Թէոդիկի «Ամէնուն տարեցոյցը» ՝ իբրեւ նամակագրական ժառանգութեան սկզբնաղբիւր - Աբրահամեան, Քնարիկ («Գիրք» հրատ.)
The article refers to one of the most visible names of the Western Armenian press of the beginning of the 20th century, to Theodig’s “Amenun Taretsuytsy” (1907-1929), particularly the correspondental heritage found in its pages. It is emphasized the fact, that the author considered the letter as one of the important columns of his journal. This is evidenced by hundreds of published letters, for many of which the periodical continues to be a source. The letters of Eghia Temirchipashyan, Hrant Asatur, Krikor Odian, Ruben Sevak and others are separated by combining and clarifying them with their later editions and creative works of the writers.
Keywords: Սփյուռքի տպագիր ժառանգություն